Bibliometric analysis of quality of life in implant-based breast reconstruction - Daneshi, Kian; Ruccia, Francesca; Merh, Radhika; Barlattani, Tommaso; Alderhalli, Raed; Clemens, Mark Warren; Khajuria, Ankur (Frontiers in Oncology, 2024)
Implant-based breast reconstruction (IBR), following mastectomy, significantly impacts patients' quality of life (QoL), necessitating accurate measurement through psychometrically robust patient-reported outcome measure (PROM) tools. This bibliometric analysis aims to discern trends, identify gaps, and evaluate use of such tools in the IBR literature.The 100 most cited publications regarding quality of life in implant-based reconstruction were identified on Web of Science, across all available journal years (from 1977 to 2024) on 10th March 2024. Study details, including the citation count, main content focus, outcome measures and usage of psychological questionnaires were extracted and tabulated from each publication. The Oxford Centre for Evidence Based Medicine (OCEBM) Levels of Evidence (LOE) of each study were assessed.The 100 most cited publications on QoL in implant-based reconstruction were identified, encompassing 64192 patients and 28114 reconstructed breasts. Citations per publication ranged from 62 to 457 (mean 124.95 ± 73.05), with the highest-cited study being authored by Al-Ghazal (n = 457). The vast majority of publications were LOE II (n = 52), representative of prospective cohort studies, systematic reviews of non-randomised studies and systematic review and meta-analysis. The number of publications for LOE V, IV, III and I was 0, 7, 41 and 0, respectively. The main content focus was 'quality of life' in 83 publications, with significant utilisation of the BREAST-Q questionnaire. Eighty publications used validated questionnaires with psychometric development.This analysis demonstrates that the research methodologies within IBR mostly consist of moderate-quality publications, however notably there was a lack of LOE I studies, underscoring a gap in high-quality research within the field. Moreover, only 62/100 used validated PROM tools. Future IBR research studies should be focussed on most robust methodologies, incorporating validated PROM tools, to optimise shared-decision making and informed consent.